UI/UX Design: Digital Learning Platform Berbasis Minimum Viable Product (MVP) dan Design Thinking - Edi Kurniawan; Nasrun Marpaung; Rohminatin Rohminatin; Nurul Rahmadani; Arya Armando Panjaitan (TAMIKA: Jurnal Tugas Akhir Manajemen Informatika & Komputerisasi Akuntansi, 2024)
In the digital era, digital learning platforms have become an essential tool in the educational process. However, the success of a platform is not only determined by the availability of content but also by a satisfying user experience. To achieve this, developers often adopt the Minimum Viable Product (MVP) strategy, which allows them to release a product with minimal features to quickly obtain user feedback. Meanwhile, the Design Thinking approach provides a framework for deeply understanding user needs. This paper combines these two approaches to designing the UI/UX for the digital learning platform "Mentor on Demand", focusing on an optimized user experience where the usability testing results are obtained with scores for Students = 6 and Mentors = 5.9 both getting Pass Results.